Estudio jurídico de las multas que impone el ministerio de relaciones laborales a los empleadores por incumplimiento de obligaciones laborales en la provincia de El Oro en la ciudad de Machala en el año 2013-2014. - Vásconez Iñaguazo, Diana Patricia (2015)
The Constitution of the Republic of Ecuador protects the rights of society in general, among these is the right of workers and in particular to protect the institutions in which they are working. The subject of research conducted is of great importance to have a basic and general knowledge about the sanctions and fines to institutions and companies imposed for breach of the obligations they have with their workers.